1979
DOI: 10.1136/ard.38.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Serum copper and its relationship to clinical symptoms in rheumatoid arthritis.

Abstract: SUMMARY Total serum copper and ultrafilterable copper levels in patients with rheumatoid arthritis were determined and related to articular index, erythrocyte sedimentation rate (ESR), and serum iron concentration. Relationships were found between serum copper and ESR, and between ultrafilterable copper and articular index. The relationship between serum copper and serum iron was found to be a drug-dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Several authors have reported diminished levels of copper during this treatment (Scudder et al, 1978a;Brown et al, 1979). The decrease of serum copper could be due to the use of corticosteroids, explaining the similar copper levels found in patients not using corticosteroid therapy.…”
Section: Serum Coppermentioning
confidence: 59%
“…Several authors have reported diminished levels of copper during this treatment (Scudder et al, 1978a;Brown et al, 1979). The decrease of serum copper could be due to the use of corticosteroids, explaining the similar copper levels found in patients not using corticosteroid therapy.…”
Section: Serum Coppermentioning
confidence: 59%
“…17 pmol/1) in R A patients compared with con trols. Raised serum Cu++ levels have also been reported [2,5,7,22], Aaseth et al [2] suggested that elevated Cu++ levels in RA might assist progression of the disease by causing tissue damage through reduction of membrane sta bility. On the other hand, copper complexes have been claimed to be efficacious in the treatment of arthritic conditions [23], How ever, no sufficient explanation for these bene ficial effects of copper has been proposed.…”
Section: Discussionmentioning
confidence: 92%
“…Increased serum copper level has been found in rheumatoid arthritis (31) and in adjuvant arthritic rats (32), providing defini tive evidence for the involvement of endoge nous copper in inflammatory disease. In this experiment, adjuvant arthritic rats also showed a marked increase in serum copper level, while cholesterol-fed rats tended to have higher levels.…”
Section: Discussionmentioning
confidence: 99%